Artificial and natural RNA interactions between bacteria and C. elegans. Issue 4 (3rd April 2017) - Braukmann, Fabian; Jordan, David; Miska, Eric
ABSTRACT: Nineteen years after Lisa Timmons and Andy Fire first described RNA transfer from bacteria to C. elegans in an experimental setting 48 the biologic role of this trans-kingdom RNA-based communication remains unknown. Here we summarize our current understanding on the mechanism and potential role of such social RNA.